Average Throughput with Linear Network Coding over Finite Fields: The Combination Network Case. (3rd April 2008) - Al-Bashabsheh, Ali; Yongacoglu, Abbas
Abstract : We characterize the average linear network coding throughput, T c avg, for the combination network with min-cut 2 over an arbitrary finite field. We also provide a network code, completely specified by the field size, achievingT c avg for the combination network.